PENGARUH PELAYANAN, INFORMASI TEKNOLOGI DAN LOKASI TERHADAP KEPUTUSAN NASABAH DALAM MEMILIH BANK SYARIAH DI YOGYAKARTA (Studi Kasus Bank BSM, BNI Syariah dan BPD Syariah) THE INFLUENCES OF SERVICE, - Muthia Melinda Sari (EKPI IE 16 UMY 027, 2016)
*27 This research aims at analyzing The Influences of Service, Information Technology and location Toward Customer’s Decision in Selecting Islamic Banks in Yogyakarta (A case study of BSM, BNI Syariah and BPD Syariah Banks). The subject in this research in customers who are in Islamic banks, especially BSM, BNI Syariah and BPD Syariah banks in Yogyakarta. In this research, the total samples are 150 respondents who were selected by using purposive sampling method. The method used was Multiple Linear Regression. Based on the analysis done, it is obtained the result partially that the variabels of service, information technology and location have positive and significant influence towards the customer’s decision in selecting Islamic banks. In the analysis simultaneously, it is obtained the result that the variables of service, information technology and location have positive and significant influence towards the customer’s decision in selecting Islamic banks. In this research, the one which dominates the customer’s decision in selecting Islamic banks is location. The existence of Islamic banks strategic location can affect customers in the decision to select Islamic banks. Key words: Islamic banks, Customer Decision, Service, Information Technology and Location.